Report of the International Society of Hypertension Teaching Seminar organized by the International Society of Hypertension Africa Regional Advisory Group: Maputo, Mozambique, 2016. Issue 10 (October 2016) - Onwubere, Basden; Coca, Antonio; Damasceno, Albertino; Kadiri, Solomon; Kruger, Ruan; Lemogoum, Daniel; M'Buyamba-Kabangu, Jene-Rene; Okpechi, Ikechi; Poulter, Neil; Rayner, Brian; Seedat, Yakoob K.; Schutte, Aletta E.; et al.
Abstract : The International Society of Hypertension (ISH), in fulfilment of its mission of promoting hypertension control and prevention and also of advancing knowledge globally, organizes hypertension teaching seminars or 'summer schools' worldwide through the ISH Regional Advisory Groups. In Africa, seven of such seminars have been organized. This is a report of the eighth seminar held in Maputo, Mozambique, April, 2016. The seminar was attended by over 65 participants from 11 African countries. The Faculty consisted of 11 international hypertension experts. The eighth African hypertension seminar was a great success as confirmed by a pre- and post-test questionnaire.